Perlindungan Hukum Bagi Investor yang Mengalami Kerugian dalam Transaksi Forex Trading Akibat Wanprestasi oleh Pialang Berjangka - Riska Aulia; Ariawan Gunadi (LPPM Universitas Ekasakti Padang, 2023)
Legal protection for investors in forex trading transactions is very important, considering that forex is one of the investment options that is in great demand because it is an investment alternative that provides high returns. Forex trading is carried out outside the Commodity Futures Exchange through an Alternative Trading System (SPA) and under the supervision of the Commodity Futures Trading Supervisory Agency (BAPPEBTI). However, currently there is misuse of Direct Sales Permits (SIUPL) on several online trading sites which are a means of carrying out forex transactions by investors. This research uses a normative research method which explains the contracts regulated in Law No. 10 of 2011 as well as CoFTRA regulations which do not balance the rights and obligations of the parties. This journal will discuss legal protection for investors who experience losses in forex transactions on online trading sites that misuse business licenses.